2003
DOI: 10.1897/1551-5028(2003)022<0276:tbamoc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Bioconcentration and Metabolism of Chlorpyrifos by the Eastern Oyster, Crassostrea Virginica

Abstract: Eastern oysters (Crassostrea virginica) were exposed to [14C]chlorpyrifos (O,O-diethyl-O-[3,5,6-trichloro-2-pyridyl] phosphorothioate) at an average measured seawater concentration of 0.6 microg/L under flow-through conditions for 28 d. The compound O,O-diethyl-O-(3,5-dichloro-6-methylthio-2-pyridyl)phosphorothioate (DMP) was extracted and identified as the single metabolite observed, and this metabolite constituted the majority of the total [14C] activity in the oyster at all sampling times. Once oysters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…It is worth mentioning that in C. gigas exposed to a mixture of pesticides containing glyphosate, its main metabolite named aminomethylphosphonic acid (AMPA) was detected in oyster tissues, probably resulting from the biotransformation of the parent herbicide in the oyster (Geret et al 2013). Moreover, the biotransformation products of other pollutants such as the PAHs, benzo(a)pyrene (Anderson 1985) and pyrene (Bustamante et al 2012) or the pesticides, chlorpyrifos (Woodburn et al 2003), and pentachlorophenol (Shofer and Tjeerdema 1993) have already been identified in the oyster Crassostrea virginica demonstrating the metabolic ability of Crassostrea species to biotransform xenobiotics.…”
Section: Fate Of Diuron In Oyster and Detoxification Processmentioning
confidence: 99%
“…It is worth mentioning that in C. gigas exposed to a mixture of pesticides containing glyphosate, its main metabolite named aminomethylphosphonic acid (AMPA) was detected in oyster tissues, probably resulting from the biotransformation of the parent herbicide in the oyster (Geret et al 2013). Moreover, the biotransformation products of other pollutants such as the PAHs, benzo(a)pyrene (Anderson 1985) and pyrene (Bustamante et al 2012) or the pesticides, chlorpyrifos (Woodburn et al 2003), and pentachlorophenol (Shofer and Tjeerdema 1993) have already been identified in the oyster Crassostrea virginica demonstrating the metabolic ability of Crassostrea species to biotransform xenobiotics.…”
Section: Fate Of Diuron In Oyster and Detoxification Processmentioning
confidence: 99%
“…In South America, the use of biomarkers in biomonitoring surveys is increasing, but not always in native species (Carriquiriborde and Bainy, 2012). The sensitivity to a toxic compound varies among species, therefore the study of biomarkers in native bioindicators is relevant (van der Oost et al, 2003). Moreover, many of the studies have exposed the organisms to high or not environmentally relevant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Bioconcentration and metabolism of chlorpyrifos by the eastern oyster was studied (Woodburn et al, 2003). The average BCF for the edible tissue portion was 1,400 ml/g.…”
Section: Sibony and Rubinmentioning
confidence: 99%